1 - The Politics of ‘Hope’ and ‘Despair’: Generational Dimensions to Igbo Nationalism in Post-Civil War Nigeria - Godwin Onuoha, (African Sociological Review, 2015)
This paper examines the concept of “generations” as one of the key features of contemporary Igbo nationalism, and as one that has received relatively less or no attention in the literature on post-civil war Igbo nationalism in Nigeria. Drawing on the activities of Ohanaeze Ndi Igbo- the apex socio-political group in Igboland- and the Movement for the Actualization of the Sovereign State of Biafra (MASSOB) - a second-generation Igbo nationalist movement this article examines the dynamics of generational tensions between youth-led and elite-led Igbo groups in Igboland. On the one hand, the political agency of Ohanaeze Ndi Igbo is traced genealogically to the imperatives of the patrimonial politics of the Nigerian state, the need to play the “politics of the centre” and re-integrate the Igbo into mainstream politics in the postcivil war era. On the other hand, the MASSOB project is rooted in the aborted secessionist war for Igbo self-determination between 1967 and 1970. It rejects a state-led process, seeks the realignment of the generational balance of power, and ultimately, an exit of the Igbo ethnic group into an alternative political and administrative arrangement. These generational differences and tensions offer insights into the transformation of local politics and the changing configurations of power and authority in present day Igboland, one that pits an emergent youth movement against an enduring Igbo establishment within the broader context of ethnic identity politics in Nigeria.